2002
DOI: 10.1515/pteridines.2002.13.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Neopterin, IgG, IgA, IgM, and Plasma Volume Changes During Long-distance Running

Abstract: Prolonged physical exercise is associated with several immunological changes, e.g. increase in proinflammatory cytokines, changes in the white blood count etc. Great discrepancies exist with regard to the exercise-induced influence on serum immunoglobulin and neopterin values. One explanation could be the shifts in plasma volume (PV) during and after exercise which might influence plasma concentrations of these parameters. Therefore we investigated the consequences of a marathon race in a homogenous group of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…As an example, Subjects in the Ganga study were marathon runners, their mean activity duration was 2.7 hour but activity duration in the present study was 30 minutes. As well as, intensity of activity in Ganga study was maximal but intensity of activity in the present study was sub maximal (70 to 75 percent of maximum heart rate) [10]. Aerobic activity in Karacabey study was 30 minutes running on treadmill with intensity 60 to 70 percent of maximal oxygen uptake that is very similar to the present study in terms of intensity and duration [18].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As an example, Subjects in the Ganga study were marathon runners, their mean activity duration was 2.7 hour but activity duration in the present study was 30 minutes. As well as, intensity of activity in Ganga study was maximal but intensity of activity in the present study was sub maximal (70 to 75 percent of maximum heart rate) [10]. Aerobic activity in Karacabey study was 30 minutes running on treadmill with intensity 60 to 70 percent of maximal oxygen uptake that is very similar to the present study in terms of intensity and duration [18].…”
Section: Discussionsupporting
confidence: 81%
“…Also, not only in the recent studies of human subjects didn't showed exact mechanism of affecting systemic immunity by sleep or sleep deprivation but also the exercises and Sleep deprivation related studies that have examined changes in immunoglobulin responses are in conflict. Some studies have shown decreases or no change [7,10,14,23,24,33,35]; some have shown increases [13, 30, 34, and 36]. Therefore, the aim of this study was determine the effect of sleep deprivation on serum IgG responses to aerobic activity in college student athletes.…”
Section: Introductionmentioning
confidence: 99%
“…The communication of T cells and macrophages and the subsequent release of neopterin makes it an effective marker of immune system activation and inflammation [21,29]. Several studies have identified the rise of neopterin in plasma and urine following exercise [30][31][32][33]. Our thought is that the damage to muscle as a result of eccentric loading and hypertrophy training will increase the amount of macrophages present at these sites, and subsequently produce higher concentrations of 7,8-dihydroneopterin which can be oxidized to neopterin.…”
Section: Neopterin and 78-dihydroneopterinmentioning
confidence: 99%
“…Reports about exercise-induced changes in serum neopterin are scarce. Neopterin was increased after moderate endurance excrcise (e.g., mountain hiking, 9) but also after exhaustive endurance exercise (e.g., bicycle marathon and long-distance run; 10,11,12). The causes for an acute phase response due to exhaustive prolonged exercise are multifaceted and complex.…”
Section: Introductionmentioning
confidence: 99%